Preoperative respiratory strength training is feasible and safe and improves pulmonary physiologic capacity in individuals undergoing cardiovascular surgeryCentral MessagePerspective - Cara Donohue, PhD, CCC-SLP; Lauren Wiele, MS, CCC-SLP; Alyssa Terry, MS, CCC-SLP; Eric Jeng, MD; Thomas Beaver, MD; Tomas Martin, MD; Terrie Vasilopoulos, PhD; Emily K. Plowman, PhD, CCC-SLP (JTCVS Open, 2023)
Objective: To determine the safety, feasibility, and physiologic impact of a preoperative respiratory strength training (RST) program in individuals undergoing elective cardiac surgery (CS). Methods: Twenty-five adults undergoing an elective CS at an academic hospital setting enrolled and completed RST 5 days/week (50 repetitions, 50% training load, ≥3 weeks) at home via telehealth in this open-label prospective cohort study. RST adherence, telehealth attendance, and adverse events were tracked. Pre- and post-RST outcomes of maximum expiratory pressure (MEP), maximum inspiratory pressure (MIP), voluntary cough spirometry, and patient-reported dyspnea were collected. Descriptive analyses and Wilcoxon signed rank-tests were performed. Results: Two participants (9%) did not complete the prescribed RST program. No significant RST-related adverse events occurred. Treatment adherence for all enrolled participants was 90%, and telehealth attendance was 99%. Of the CS patients who completed the prescribed program (n = 23; 91%), treatment adherence and telehealth attendance were excellent (98% and 100%, respectively). Significant increases in primary outcomes were observed: MEP mean change, +15.4 (95% confidence interval [CI], +3.4 to +27.3, P < .007); MIP mean change, +14.9 (95% CI, +9.4 to +20.4, P < .0001). No statistically significant differences in voluntary cough or perceived dyspnea outcomes were observed (P > .05). Conclusions: These preliminary data demonstrate that a preoperative RST program is safe and feasible and can improve short-term respiratory physiologic capacity (MEP and MIP) in CS patients. Future research is warranted to validate the current findings in a larger cohort of CS patients and to determine whether RST improves postoperative extubation outcomes, airway clearance capacity, and aspiration following cardiac surgery.